Genetic Architecture of Sexual Dimorphism in Humans. Issue 10 (October 2015) - Rigby, Nichole; Kulathinal, Rob J.
<x xml:space="preserve">Abstract</x> Males and females differ across a broad spectrum of morphological, physiological, and behavioral characters. In fact, sexually dimorphic traits typically contribute the largest component of phenotypic variance in most taxa that use sex to reproduce. However, we know very little about the mechanisms that maintain these dimorphic states and how these sexually dimorphic traits evolve. Here, we review our current knowledge of the underlying genetic basis of sexual dimorphism in humans. First, we briefly review the etiology of sex differences starting from sex determination's initial switch early in embryogenesis. We then survey recent sex‐biased transcriptomic expression literature in order to provide additional insight into the landscape of sex‐biased gene expression in both gonadal and non‐gonadal tissues: from overall prevalence to tissue specificity to conservation across species. Finally, we discuss implications of sex‐biased genetic architecture to human health and disease in light of the National Institute of Health's recently proposed initiative to promote study samples from both sexes. J. Cell. Physiol. 230: 2304–2310, 2015. © 2015 Wiley Periodicals, Inc.